Effects of Senility on Disease Burden: Panel Analysis Using 2010 to 2019 OECD Health Data - Heesun Kim; Eun-Jung Kim (SAGE Publishing, 2023)
Background: In this study, the geniatric status of OECD (Organisation for Economic Co-operation and Development) countries was measured, and the effects of aging status on disease patterns in each country were quantitatively assessed. A theoretical model explaining the effects was suggested, and the implications were discussed. Methods: Data used in this study were the OECD Health Statistics data and WHO Global Burden of Disease data. The values for each country were paired with disability-adjusted life years (DALYs) presented by the WHO and Institute for Health Metrics and Evaluation (IHME). A cross-country panel analysis was conducted to analyze the effects of senility on the burden of disease in OECD countries. Results: Geniatric status had effects on the burden of disease ( P  = .048). Total health expenditure significantly reduced the burden of disease ( P  = .001). In the panel model with YLL (Year of Life Lost) as the outcome variable, geniatric status had twice greater effects on the burden of disease than that in the model with DALY ( P  = .003). Conclusions: In medical insurance-related policies, the characteristics of the disease should be considered. In particular, chronic diseases have not received much attention compared to their risk. However, the disease that actually affects the burden of disease is a disease that becomes chronic and requires long-term treatment rather than a disease with a high fatality rate. And, as a result of this study, the higher the level of resource consumption for treatment in OECD countries, where aging is progressing, the burden of disease was rather reduced. Therefore, if there is institutional support to receive appropriate treatment, it will be possible to reduce the national burden of disease.